Integrating taxonomic, genetic and ecological data to explore the species richness of wild bees (Hymenoptera, Apoidea, Anthophila) of the Culuccia Peninsula (NE Sardinia, Italy) - Matteo Annessi; Alessandra Riccieri; Marilena Marconi; Sabrina Rossi; Andrea Di Giulio (Journal of Hymenoptera Research)
Wild bees are essential pollinators of both native and cultivated plants, but their populations are declining worldwide. Conservation efforts are hindered by insufficient data, especially in the Mediterranean basin, which hosts some of the most diverse pollinator communities in the world. Particularly in Sardinia, the second largest island in the Mediterranean, information on the bee fauna is still limited. The aim of this work was to provide the first checklist of Apoidea Anthophila from an unexplored peninsula in north-eastern Sardinia (Italy), by combining traditional (morphologically-based) taxonomy and DNA barcoding. In addition, records of flower visits are provided and shown in a visitor network to enrich the scarce data on the associations between wild bees and plants in the Mediterranean Region. Bees were sampled from April to October 2022–2023 with two Malaise traps and nets. DNA was extracted to amplify sequences of the mitochondrial gene Cyotochrome oxydase I, which were then compared with those in BOLD using the identification tool and by constructing neighbor-joining phylogenetic trees. Seventy-six different species belonging to 29 genera and six families were collected and identified. A total of 212 COI sequences were obtained for 61 different species, many of which had not yet been sequenced from Italian populations. Five of the collected taxa are Sardo-Corsican endemics, whereas six species are newly recorded from Sardinia. Finally, we highlight potential taxonomic issues and new flower visit records, emphasizing the need for further research to better understand the taxonomy and ecology of this diverse group of insects toward their conservation.